A comunicação sindical: as redes digitais como espaço para a formação política dos professores em Sergipe - Linhares, Maria Conceição da Silva (2019)
This thesis entitled ―The Union communication in facebook digital network as a space for the political training of teachers in Sergipe: the SINTESE as a case study‖, menages to study the contribution of union communication and, in particular, the one made by digital media, specifically, facebook, for the political formation of teachers represented by the Union of Workers in Basic Education of the Official Network of the State of Sergipe - SINTESE. The object of the research was built from the question whether the digital networks used by the union perform a communication processes that contributes to the political formation of teachers. Our hypothesis is that the digital networks of teachers; unions in the State of Sergipe are spaces of communication that accommodate information, production and interaction processes, and that their structuring and use can serve as a locus for the political formation of their users. To develop the research we draw the following objectives: To discuss the role of communication for the political formation of workers from the union organization movement; discuss the importance of information and communication tools of the union in strengthening the political formation of teachers; investigate the function and use of digital networks of SINTESE, considering the content, access and communication strategies towards the political formation of teachers. The theoretical-methodological procedures, based on historical-dialectical materialism, supported the study of union communication of SINTESE in two aspects of analysis: 1) Immersion in official and extra official documents, socialized in the union's digital social networks to identify in the conception of education required by the union, the direction of its communication policy, as well as the place of Communication and its role in political formation. of teachers; 2) Immersion in the SINTESE facebook social network focusing on content, communication strategies and interaction between the union and teachers to identify their contribution to the political formation of teachers. Considering the nature of the object, we‘ve tried to examine it from a variety of instruments and techniques such as content analysis, document analysis, analysis of digital communication networks. As a result of the research, we‘ve infered that SINTESE intends in its communication actions to use its instruments to inform, communicate and train. However, we‘ve identified on the facebook social network some problems that indicate the need to improve teachers' participation and union mediation from the content available. Important processes for the formation and the socio-political practice, so much needed today.________________________________________________________________________________________________________________________________